ISLAM DAN INDONESIA MODERN DALAM PERSPEKTIF TEOLOGI INKLUSIF NURCHOLIS MADJID - Said Subhan Posangi (Farabi, 2018)
Cak Nur's thought in theological matters is more of a representation of the views of the latter which emphasize the need reorientation of religious understanding to the present empirical reality. Cak Nur, in his book, Islamic Doctrine and Civilization, this attitude is clear he said that religious normative provisions could be attempted seen in the possibility of its social- historical implementation. Because, after all the height of a teaching, but what is actually in it human life and influencing society is a form of implementation concretely in history, namely the social and cultural life of humans time and space context